Protein Restriction in the Peri-Pubertal Period Induces Autonomic Dysfunction and Cardiac and Vascular Structural Changes in Adult Rats - Ferreira, Anna Rebeka Oliveira; Ribeiro, Maiara Vanusa Guedes; Peres, Maria Natalia Chimirri; Piovan, Silvano; Gonçalves, Géssica Dutra; Saavedra, Lucas Paulo Jacinto; Martins, Juliana Nunes de Lima; Junior, Marcos Divino Ferreira; Cavalcante, Keilah Valeria Naves; Lopes, Gabriel kian Guimarães; Carneiro, Mariane; Almeida, Douglas Lopes; et al. (Frontiers in Physiology, 2022)
Perturbations to nutrition during critical periods are associated with changes in embryonic, fetal or postnatal developmental patterns that may render the offspring more likely to develop cardiovascular disease in later life. The aim of this study was to evaluate whether autonomic nervous system imbalance underpins in the long-term hypertension induced by dietary protein restriction during peri-pubertal period. Male Wistar rats were assigned to groups fed with a low protein (4% protein, LP) or control diet (20.5% protein; NP) during peri-puberty, from post-natal day (PN) 30 until PN60, and then all were returned to a normal protein diet until evaluation of cardiovascular and autonomic function at PN120. LP rats showed long-term increased mean arterial pressure (p=0.002) and sympathetic arousal; increased power of the low frequency (LF) band of the arterial pressure spectral (p=0.080) compared with NP animals. The depressor response to the ganglion blocker hexamethonium was increased in LP compared with control animals (p=0.006). Pulse interval variability showed an increase in the LF band and LF/HF ratio (p=0.062 and p=0.048) in LP animals. The cardiac response to atenolol and/or methylatropine and the baroreflex sensitivity were similar between groups. LP animals showed ventricular hypertrophy (p=0.044) and increased interstitial fibrosis (p=0.028) compared with controls. Reduced protein carbonyls (PC) (p=0.030) and catalase activity (p=0.001) were observed in hearts from LP animals compared with control. In the brainstem, the levels of PC (p=0.002) and the activity of superoxide dismutase and catalase (p=0.044 and p=0.012) were reduced in LP animals, while the levels of GSH and total glutathione were higher (p=0.039 and p=0.038) compared with NP animals. Protein restriction during peri-pubertal period leads to hypertension later in life accompanied by sustained sympathetic arousal, which may be associated with a disorganization of brain and cardiac redox state and structural cardiac alteration.